An Analysis of Kitābah Teaching Strategies for Fourth Grade Students in Elementary Arabic Education - Yulia Zulpathul Aizza; Yuyun Rohmatul Uyuni; Rohanda Rohanda (UIN Sunan Gunung Djati Bandung, 2026)
Kitābah (Arabic writing) instruction plays a crucial role in developing students' productive language skills; however, its implementation at the elementary level remains constrained by limited instructional strategies and low student proficiency. Previous studies have mainly focused on learning media, online instruction, or error analysis, leaving a gap in context-based kitābah strategies in primary education. This study aims to analyze the implementation of kitābah learning strategies and their contribution to improving students' writing skills. Using a descriptive qualitative approach, the study involved an Arabic teacher and fourth-grade students at SD Bani Daud Al-Islami Petir. Data were collected through observations, interviews, and documentation, and analyzed using an interactive model. The findings indicate that effective kitābah instruction involves integrating communicative approaches, guided practice, visual media, and linking writing with reading (qirā’ah) and speaking (muḥādathah). These strategies enhance student engagement, support grammatical understanding, and improve sentence construction. Additionally, structured learning stages and the use of student worksheets (LKPD) contribute to consistent skill development. This study highlights the importance of student-centered, structured instructional design for improving Arabic writing skills. Future studies are recommended to examine these strategies using quantitative or mixed-method approaches.